2017
DOI: 10.1128/mbio.02320-16
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Tagged nsp15 Reveals Interactions with Coronavirus Replication/Transcription Complex-Associated Proteins

Abstract: Coronavirus (CoV) replication and transcription are carried out in close proximity to restructured endoplasmic reticulum (ER) membranes in replication/transcription complexes (RTC). Many of the CoV nonstructural proteins (nsps) are required for RTC function; however, not all of their functions are known. nsp15 contains an endoribonuclease domain that is conserved in the CoV family. While the enzymatic activity and crystal structure of nsp15 are well defined, its role in replication remains elusive. nsp15 local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 51 publications
(76 reference statements)
6
51
1
Order By: Relevance
“…Remarkably, Nsp15 binds to the Nsp7/Nsp8 complex with a stronger affinity than to Nsp8. In contrast to previous IP results (20), both the pulldown and MST assays could not detect an interaction between Nsp15 and Nsp12, possibly due to extremely weak interaction. Moreover, given that Nsp12 can complex with Nsp8 and Nsp7 (20), another possible explanation might be that the detected interaction between Nsp12 and Nsp15 by IP was a result of the indirect binding of Nsp12 with Nsp8 instead of the direct binding with Nsp15.…”
Section: Discussioncontrasting
confidence: 99%
“…Remarkably, Nsp15 binds to the Nsp7/Nsp8 complex with a stronger affinity than to Nsp8. In contrast to previous IP results (20), both the pulldown and MST assays could not detect an interaction between Nsp15 and Nsp12, possibly due to extremely weak interaction. Moreover, given that Nsp12 can complex with Nsp8 and Nsp7 (20), another possible explanation might be that the detected interaction between Nsp12 and Nsp15 by IP was a result of the indirect binding of Nsp12 with Nsp8 instead of the direct binding with Nsp15.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies reported that coronavirus dsRNA associates with replication complexes early during infection and is buried in DMVs, which are thought to protect viral RNA from host sensors (8,9,43). Additionally, our group and others have shown that nsp15 also associates with replication complexes (44,45) and interacts with single-strand RNA and dsRNA (13). Therefore, we hypothesized that that nsp15 may function to maintain the asso-ciation of dsRNA with replication complexes.…”
Section: Mhv Nsp15 Mutant Viruses Trigger Rapid Apoptotic Cell Death Inmentioning
confidence: 94%
“…The RNA was transcribed into cDNA using Moloney murine leukemia virus reverse transcriptase (MMLV RT) (Thermo Fisher Scientific). Subgenomic RNA levels were measured on a QuantStudio qPCR 3 system (Thermo Fisher Scientific) using previously described subgenomic RNA primers (41). The levels of subgenomic RNA were normalized to hypoxanthine-guanine phosphoribosyltransferase (HPRT) by the following threshold cycle (C T ) equation: ΔC T ϭ C T of gene of interest Ϫ C T of HPRT.…”
Section: Methodsmentioning
confidence: 99%